2018
DOI: 10.31957/jbp.569
|View full text |Cite
|
Sign up to set email alerts
|

Domestifikasi Anggrek di Distrik Merauke Kabupaten Merauke–Papua

Abstract: Inventory study of cultivated orchid in District Merauke, Merauke City was done from March–June 2006.  Survey methods was used in this study. There were ten species of orchid in this area, consisted of 8 species of native Papuan orchids (Acriopsis javanica Reinw, Dendrobium anthenatum, Dendrobium diskolour Lind, Dendrobium konkolor Lind, Dendrobium nindii, Dendrobium johanes, and two hibrids), and 2 introduce species (Phalaenopsis sp and Phalaenopis amabilis). Dendrobium anthenatum, Dendrobium diskolour Lind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The interview results also show that people maintain dendrobium orchids because of their large and brightly colored flowers. As stated by Burok et al [13], dendrobium orchids are easy to maintain because they are easy to adapt to the growing media used by the community and are easy to grow. Haniva et al [14] also mentioned that, dendrobium orchids are ornamental plants that are popular among the public because of the beauty of their flowers.…”
Section: Realolo Hamletmentioning
confidence: 99%
“…The interview results also show that people maintain dendrobium orchids because of their large and brightly colored flowers. As stated by Burok et al [13], dendrobium orchids are easy to maintain because they are easy to adapt to the growing media used by the community and are easy to grow. Haniva et al [14] also mentioned that, dendrobium orchids are ornamental plants that are popular among the public because of the beauty of their flowers.…”
Section: Realolo Hamletmentioning
confidence: 99%
“…Di Papua, keragaman anggrek cukup tinggi (Millar, 1978;Sihombing & Lestari, 2002). Hasil penelitian telah dilaporkan oleh Agustini et al (2010) yang dilakukan di Papua Selatan, Burok et al (2009) khususnya di Merauke, Lugrayasa (2004) di sekitar Cycloops Jayapura, dan Ungirwalu et al (2007) di Sorong Selatan. Beberapa jenis anggrek diketahui mempunyai distribusi yang luas di Papua, seperti Spatoglottis sp.…”
Section: Jenis-jenis Anggrekunclassified
“…Research conducted by Burok et al (2009) revealed that many orchid species in Merauke District have not yet been known in detail, suggesting that further taxonomical work is required. The study also explained that only 10 species of orchids had been domesticated by the communities.…”
Section: Introductionmentioning
confidence: 99%